OUTCOMES ASSOCIATED WITH HOME AND COMMUNITY-BASED SERVICE TYPE AMONG OLDER MONEY FOLLOWS THE PERSON PARTICIPANTS. (16th November 2018) - Fabius, C; Shugrue, N; Robison, J
Abstract: There is a growing demand for home and community-based services (HCBS) that enable older adults to age in the community. However, there remains a lack of research regarding the type of HCBS individuals are using, and the effect of service use on health care utilization and quality of life outcomes. This study describes three types of HCBS services and estimates the effect of service type on nursing home readmission and global life satisfaction among 880 older (aged 65+) Connecticut Money Follows the Person Rebalancing Demonstration participants. The three HCBS categories include: traditional HCBS (homemaker, companion, home health, home-delivered meals, adult day center); personal care attendant (PCA; includes hands-on help with daily living activities), and 24-hour live-in care. Bivariate analyses indicate several demographic and quality of life differences across HCBS categories. Participants using traditional HCBS were more often younger, male, non-White, had fewer ADL/IADL impairments, and higher choice and control scores as well as greater global life satisfaction compared to individuals using PCA or 24-hour live-in care services. Participants receiving live-in care reported receiving less help from family and friends. Binary logistic regression models indicate that HCBS type is associated with nursing home readmission, but not global life satisfaction 12 months after transitioning into the community. Participants with PCA and 24-hour live-in services were less likely to be readmitted to nursing home at 12 months compared to those with traditional HCBS. Results from this study have implications for improving HCBS delivery for older adults living in the community.